Volume 4: Fluid Structure Interaction 2005
DOI: 10.1115/pvp2005-71464
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Excitation Force Measurements in a Rotated Triangular Tube Bundle Subjected to Two-Phase Cross Flow

Abstract: Two-phase cross flow exists in many shell-and-tube heat exchangers. Flow-induced vibration excitation forces can cause tube motion that will result in long-term fretting-wear or fatigue. Detailed vibration excitation force measurements in tube bundles subjected to two-phase cross flow are required to understand the underlying vibration excitation mechanisms. An experimental program was undertaken with a rotated-triangular array of cylinders subjected to air/water flow to simulate two-phase mixtures over a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 0 publications
1
16
2
Order By: Relevance
“…The occurrence of these phenomena depends on the flow regime, which is associated with physical properties of fluids, inlet flow conditions, local void fraction, and flow channel geometries. Cross flow two-phase FIV exists in shell-and-tube heat exchangers (Mitra et al, 2009;Sasakawa et al, 2005;Zhang et al, 2007;Kanizawa et al, 2012) and U-tube region in PWR steam generators (Pettigrew et al, 1998). With regards to internal two-phase FIV, flow turning elements are considered as one of the major sources for causing FIV by generating sudden change in momentum flux, pressure fields, or creating secondary vortices due to boundary layer separation (Belfroid et al, 2010;Cargnelutti et al, 2010;Pontaza and Menon, 2011;Yamano et al, 2011).…”
Section: Flow-induced Vibration In Nuclear Reactor Systemsmentioning
confidence: 99%
“…The occurrence of these phenomena depends on the flow regime, which is associated with physical properties of fluids, inlet flow conditions, local void fraction, and flow channel geometries. Cross flow two-phase FIV exists in shell-and-tube heat exchangers (Mitra et al, 2009;Sasakawa et al, 2005;Zhang et al, 2007;Kanizawa et al, 2012) and U-tube region in PWR steam generators (Pettigrew et al, 1998). With regards to internal two-phase FIV, flow turning elements are considered as one of the major sources for causing FIV by generating sudden change in momentum flux, pressure fields, or creating secondary vortices due to boundary layer separation (Belfroid et al, 2010;Cargnelutti et al, 2010;Pontaza and Menon, 2011;Yamano et al, 2011).…”
Section: Flow-induced Vibration In Nuclear Reactor Systemsmentioning
confidence: 99%
“…Two-phase FIV on cross flow exists in shell-and-tube heat exchangers (Kanizawa et al, 2012;Khushnood et al, 2004;Mitra et al, 2009;Nakamura et al, 1986Nakamura et al, , 1992Pettigrew and Knowles, 1997;Sasakawa et al, 2005;Zhang et al, 2007), U-tube region in the pressurized water reactor (PWR) steam generators (Pettigrew et al, 1998), and offshore structures (JSME, 2003). Cross flow generally involves either isolated cylinder or bundles of cylinders.…”
Section: Two-phase Cross Flowmentioning
confidence: 98%
“…Conversely, only few experimental data for turbulence-induced vibration mechanism under conditions twophase flow are available, which is somehow surprising since this vibration mechanism is unavoidable, and is always present in heat exchanger tube bundles. Actually, more recent experimental studies (ZHANG et al, 2007;PERROT et al, 2011) have shown that there is a lack of knowledge in this mechanism since they found out that it consists of turbulence and periodic components, which have not been reported in literature before.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulties, several methodologies to measure flow -induced forces in tube bundles have been proposed. For example, Zhang et al (2007) measured dynamic forces on both directions, transverse and parallel to flow main velocity, via strain gauge instrumented cylinders. In order to do that, the instrumented tubes were designed so that the fundamental natural frequency was higher than 150 Hz, which is considerably higher than both the expected force frequencies to be analyzed and the range of tube resonance frequencies in real heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation